Extraction, Modelling and Purification of Flavonoids from Citrus Medica Peel - Nandan, M. Parvathi; Meena, Vangalapati (International Journal of Applied Sciences and Biotechnology, 2015)
Soxhlet extraction technique is widely employed for the extraction and separation of chemical constituents in the medicinal plants. Citrus medica L commonly called as Citron belongs to family Rutaceae, is a slow-growing shrub. It is mainly cultivated for the production of edible fruits which are sour in taste like lime and lemon and the main content of a citron fruit is the thick rind, which is very adherent to the segments. From the phytochemical analysis the peel extract is rich source of phenols, flavonoids and alkaloids. The objective of present work is to develop a modelling equation for quercetin, rutin and kaempferol and the crude extract obtained by soxhlet extraction was further purified by solvent-solvent extraction and Column chromatography. Extraction was carried out by 80% methanol as a solvent Soxhlet extractor. Soxhlet extraction with methanol was carried out with varying time intervals, to evaluate modelling equation. The proposed modelling equation was Es = 0.0849(t) + 7.0286 for Quercetin and Es = 0.0912(t) + 25.971 for rutin, and Es = 0.0267(t) + 7.3714 for Kaempferol. High yield was obtained for 180min of Soxhlet extraction with 80% methanol. Yield of quercetin, rutin and kaempferol after solvent-solvent extraction and column chromatography was 22.6µg/ml, 43.7µg/ml and 10.8µg/ml respectively. The proposed model showed good agreement with the experimental data. Int J Appl Sci Biotechnol, Vol 3(4): 588-591